Recognition of Animal Pain: Phenomenological Reflections - Olivier, Abraham (Theoria (Pietermaritzburg), 2024)
Animal pain and suffering is mostly caused by humans, particularly by the human use of domestic animals. This calls for the recognition of animal pain and suffering. My focus is on pain-related suffering. I argue for recognition in the phenomenological sense of giving adequate regard to pain experience in animals and their capacity to express it in their own species-specific terms, in a way that will motivate us to prevent it. My advocacy for the recognition of pain in animals consequently includes a consideration of moral and political action to avert their suffering.